PAPEL: A lexical ontology for Portuguese - Gonçalo Oliveira, Hugo; Santos, Diana; Gomes, Paulo; Seco, Nuno (My University, 2008)
PAPEL is a lexical resource for natural language processing (NLP) of Portuguese which is being built by Linguateca, based on processing a major commercial Portuguese dictionary, the Dicionário da Língua Portuguesa (DLP) developed and owned by the largest Portuguese dictionary publisher, Porto Editora. As far as we know, PAPEL is the first lexical ontology built by semi-automatic means for Portuguese. We are currently working on CAUSADOR-DE/RESULTADO-DE, TODO-DE/PARTE-DE and MEIO-PARA/FINALIDADE-DE semantic relations, that can be extracted using the PEN parser and specific grammars consisting of string patterns.
Keywords: PAPEL